A study on seasonal variation and algal biodiversity in Sulur pond, coimbatore, tamil nadu. - MANGAIYARKARASI.A; GEETHA RAMANI.D; HELEN LAWRENCIA.G; NAVEENA .M (International Journal of Pharma and Bio Sciences, 2017)
Microalgae are photosynthetic unicellular organisms that are diversified in aquatic and terrestrial environments. Algae can effectively fix Co2 for photosynthesis which in turn yields biodiesel, bioactive compounds, nutritive lipids, proteins, carbohydrates. The distribution of algae is vast but only few of the species were utilized for commercial purposes. In order to exploit the biotechnological applications, the present study aims to evaluate the biodiversity and distribution of different algal genera and the impact of seasonal variations and environmental factors on algal biodiversity in fresh water environment. Seasonal Diversity of algae and physicochemical parameters from five different sites in three different seasons in the year 2016 in Sulur pond, Coimbatore, Tamil Nadu, India were investigated. The diversity of Chlorophyceae, Cyanophyceae and Bacillariophyceae were found in all the season. The diversity of diatoms was observed to be dominant at the percentage of 54% in monsoon followed by green algae at the percentage of 26% in winter and blue green algae at the percentage of 16% during summer. The distribution of Nannochloropsisoculata of Eustigmataceae, Tribonema minus of Xanthophyceae, Porterinemafluviatile of Phaeophyceae and Cosmariumdepressum of Desmidiaceae were observed at 1% throughout the study. Seasonal changes and water quality have a direct impact on algal diversity and the concentration of nutrients plays a major role in determining the existence of different genera of algae. Among the different families of algae, Chlorophyceae, Cyanophyceae and Bacillariophyceae, were found to be dominant in Sulur pond. The study reveals the rich algal biodiversity of the sampling site and the obtained isolates could be screened to exploit their biotechnological applications.